Desempenho de fundos multimercados - Malaquias, Rodrigo Fernandes (2012)
The aim of this study was to analyze the performance of Brazilian multimarket investment funds, using a measure that is more adequate to the characteristics of their returns distribution. Given that these class involve the Brazilian funds which most resemble the foreign hedge funds, traditional measures such Sharpe’s Ratio and Jensen’s Alpha may not be appropriate to analyze the ability of its managers to add extraordinary value. The measure used is related to the paper of Amin and Kat (2003), which compares the expected return of the fund with the returns generated by a strategy that, in the absence of arbitrage, has no cost to be implanted and yields a risk-free rate. With monthly data of 107 multimarket funds in the period from January 2005 to August 2011, the main results showed that the average net performance of the funds was lower than zero. On the other hand, the average gross performance (measured with returns before management fees and performance) was statistically greater than zero, indicating that managers can add extraordinary value, but these gains are eroded by management and performance fees. The work also showed that periods of crisis not only have a significantly (and negative) impact on the performance of the funds, but also on the relationship of this performance with its determinants. Thus, the results of this work may have important contributions to the development of the theory on investment fund performance in Brazil, both because it involves the use of a more adequate analysis tool and considers the crisis as a variable that moderates the relationship between performance and its determinants.